Hybrid Robust Sliding Mode and PI-Controller for Stand-Alone Object’s Power Supply; Electron Devices and Materials (EDM) - Lyapunov D. Yu. Danil Yurievich; Fedyanin A. L. Alexander Leonidovich; Fam Chong Khay; Pravikova A. A. Alexandra; Shilin A. A. Aleksandr Anatoljevich; Kremzukov Yu. A. Yury Aleksandrovich (2024, 2024)
Заглавие с экрана